2013
DOI: 10.3727/096368912x658728
|View full text |Cite
|
Sign up to set email alerts
|

A Preexistent Hypoxic Gene Signature Predicts Impaired Islet Graft Function and Glucose Homeostasis

Abstract: We examined whether hypoxic exposure prior to the event of transplantation would have a positive or negative effect upon later islet graft function. Mouse islets exposed to hypoxic culture were transplanted into syngeneic recipients. Islet graft function, b-cell physiology, as well as molecular changes were examined. Expression of hypoxia-response genes in human islets pre-and posttransplant was examined by microarray. Hypoxia-preexposed murine islet grafts provided poor glycemic control in their syngeneic rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 47 publications
4
46
0
Order By: Relevance
“…Nevertheless, we showed that low oxygen tension significantly damages NPI function, metabolism and viability from 2 to 7 days of culture. In keeping with the literature describing the impact of ischemia or hypoxia on human pancreatic islets (Brandhorst et al, ; Cantley et al, ; Giuliani et al, ; Hals, Rokstad, Strand, Oberholzer & Grill, ; Lai et al, ; Moritz et al, ), our results suggest that the innovative oxygen supply strategy developed in the present study may also meet the challenges of hypoxia during allotransplantation of macroencapsulated human pancreatic islets.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, we showed that low oxygen tension significantly damages NPI function, metabolism and viability from 2 to 7 days of culture. In keeping with the literature describing the impact of ischemia or hypoxia on human pancreatic islets (Brandhorst et al, ; Cantley et al, ; Giuliani et al, ; Hals, Rokstad, Strand, Oberholzer & Grill, ; Lai et al, ; Moritz et al, ), our results suggest that the innovative oxygen supply strategy developed in the present study may also meet the challenges of hypoxia during allotransplantation of macroencapsulated human pancreatic islets.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, another potential mechanism by which resistin may impact on beta cell function is by enhancing blood flow to the pancreas (Danielsson et al 2009). Beta cell function is negatively impacted by hypoxia (Cantley et al , 2013 and hypoxia-inducible factor 1a activation (Cantley et al 2009); therefore, as nutrient stimulation can lead to a transient decrease in oxygen tension (Bensellam et al 2012), resistin may help to sustain adequate islet perfusion and oxygenation during times of high-metabolic demand. Furthermore, as the development of an adequate beta cell mass is highly dependent on vascular perfusion (Reinert et al 2013), resistin may potentially play a role in beta cell development and expansion.…”
Section: Resistinmentioning
confidence: 99%
“…There are recent data indicating that early hypoxic exposure may result in a persistent change in the human islet cell gene signature and longer-lasting loss of glucose-stimulated insulin secretion. 21,22 This becomes even more important if the islet does not completely revascularize, since this would mean that the islet would rely on passive oxygen transport for several days or weeks and possibly indefinitely. It is generally believed that revascularization takes 7-10 days.…”
Section: Effect Of Poor Oxygenation On Islet Survival and Functionmentioning
confidence: 99%